A Cloud-based Protection approach against JavaScript-based attacks to browsers. (May 2018) - Hsu, Fu-Hau; Hwang, Yan-Ling; Lee, Chia-Hao; Lin, Chieh-Ju; Chang, KaiWei; Huang, Chen-Chia
Abstract: JavaScript is a standard of client-side scripting languages. Due to its cross-platform property, JavaScript is widely used in web pages. Hence its security problems can seriously influence the security of devices executing code written by it. This paper proposes aC loud-basedP rotection approach againstJ avaScript-based attacks to browsers, called CPJ. CPJ provides timely and effective protection to web browsers to cope with attackers' continuously developing new JavaScript-based attack approaches. CPJ integrates VirusTotal, a cloud-based security analysis service, into a browser. Therefore, with the latest malware signature databases, it can analyze the behavior of a variety of JavaScript files. It allows a browser to block malicious code when the browser is surfing the Internet. We demonstrate its feasibility using Internet experiments, and show its effectiveness on a variety of suspicious targets. According to our experiments, CPJ has rather good sensitivity and performance.